The Effect of Material Composition of Paving Blocks from Plastic Waste on Compressive Strength and Water Absorption - Nurkhaerani, Fatma; Debora, Fransisca; Sari, Gina Lova; Nugroho, Eka Oktariyanto; Pradoto, Rani G. K.; Syakira, Hana (Jurnal Kajian Ruang, 2025)
Abstract. Waste volume in Karawang City that can be handled will only be 40% and the other 60% will be managed by waste banks and temporary shelter. Innovation in waste recycling is needed, one of which is making plastic waste as raw material for paving block production. This research aims to assess how using plastic waste as a material in making paving blocks affects their compressive strength and water absorption, with the potential to reduce overall plastic waste and explore alternatives to conventional materials. This research focuses on testing water absorption capacity and compressive strength based on SNI 03–0691–1996 standards for making paving blocks. The water absorption test results on PVG 1 and 2 are up to 38.46% larger than PVG 3 and 4 because there are many cavities in PVG 1 and 2 that making were below standard, and PVG 3 and 4 were at quality standard level B. The compressive quality test of PVG 1 and 2 have a more noticeable compressive quality regard with a typical regard of 6,075 MPa compared to clearing squares with a full plastic composition with an ordinary regard of 4,745 MPa. It happens since of insufficient and manual burning, but it can too be caused by an ought to utilize plastic waste and the got to age the clearing squares being attempted. When compared with the quality Indonesian National Standard (SNI 03 - 0691 – 1996), the compressive quality test of the clearing inside the examination did not meet the standard.Keywords: Plastic Waste, Paving Block, Water Absorption Test, Compressive Strength